112k views
5 votes
Solve the equation 18y-6y+22=11(y-2)+y

User Cryckx
by
5.6k points

1 Answer

7 votes

Answer:

the answer its 44=0

Explanation:

18y-6y+22=11(y-2)+y1

We move all terms to the left:

18y-6y+22-(11(y-2)+y1)=0

We add all the numbers together, and all the variables

12y-(11(y-2)+y1)+22=0

We calculate terms in parentheses: -(11(y-2)+y1), so:

11(y-2)+y1

We add all the numbers together, and all the variables

y+11(y-2)

We multiply parentheses

y+11y-22

We add all the numbers together, and all the variables

12y-22

Back to the equation:

-(12y-22)

We get rid of parentheses

12y-12y+22+22=0

We add all the numbers together, and all the variables

44=0

are not solution for this equation

Hope helps you and have a great day !

User Martineau
by
6.1k points